2009
DOI: 10.4081/jlimnol.2009.16
|View full text |Cite
|
Sign up to set email alerts
|

Fine scale analysis of shifts in bacterial community structure in the chemocline of meromictic Lake Cadagno, Switzerland

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
30
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 41 publications
0
30
1
Order By: Relevance
“…In Lake Cadagno, the chemocline is typically found at a depth of about 12 m and is characterized by the presence of a dense community of anaerobic phototrophic sulfur bacteria, including purple sulfur bacteria (PSB) of the genera Chromatium, Lamprocystis, Thiocystis and Thiodictyon and green sulfur bacteria (GSB) of the genus Chlorobium (Tonolla et al ., , , ). From 1998 to 2004 the total concentration of phototrophic sulfur bacteria increased from 4.9 (± 0.2) to 14 (± 1.4) 10 6 cells mL −1 , primarily due to a remarkable rise in the population of the GSB Chlorobium clathratiforme (Decristophoris et al ., ; Gregersen et al ., ). Previous reports have shown that despite its small volume (approximately 10% of the lake), the chemocline of Lake Cadagno is responsible for up to 40% of the total inorganic carbon photo‐assimilation (Camacho et al ., ).…”
Section: Introductionmentioning
confidence: 98%
“…In Lake Cadagno, the chemocline is typically found at a depth of about 12 m and is characterized by the presence of a dense community of anaerobic phototrophic sulfur bacteria, including purple sulfur bacteria (PSB) of the genera Chromatium, Lamprocystis, Thiocystis and Thiodictyon and green sulfur bacteria (GSB) of the genus Chlorobium (Tonolla et al ., , , ). From 1998 to 2004 the total concentration of phototrophic sulfur bacteria increased from 4.9 (± 0.2) to 14 (± 1.4) 10 6 cells mL −1 , primarily due to a remarkable rise in the population of the GSB Chlorobium clathratiforme (Decristophoris et al ., ; Gregersen et al ., ). Previous reports have shown that despite its small volume (approximately 10% of the lake), the chemocline of Lake Cadagno is responsible for up to 40% of the total inorganic carbon photo‐assimilation (Camacho et al ., ).…”
Section: Introductionmentioning
confidence: 98%
“…Purple sulfur bacteria were the most abundant bacteria in the chemocline between 1994 and 2001, representing between 70% and 95% of the phototrophic sulfur bacteria community (Tonolla et al, 2003). A shift in dominance from purple sulfur bacteria to green sulfur bacteria was observed between 2001 and 2003, with the species Chlorobium clathratiforme reaching about 95% of the phototrophic sulfur bacteria (Tonolla et al, 2003(Tonolla et al, , 2005Decristophoris et al, 2009;Gregersen et al, 2009;Habicht et al, 2011). It was suggested that a disruption to the chemocline in 2000 owing to natural causes (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…It was suggested that a disruption to the chemocline in 2000 owing to natural causes (i.e. a violent storm) may have altered environmental niches and populations in subsequent years (Tonolla et al, 2005;Decristophoris et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, a remarkable variability in metabolic rates of individual cells of the same species was measured, revealing that a microbial population is composed by a heterogeneous group of physiologically distinct individuals (Musat et al, 2008). In the chemocline of the oligotrophic Lake Cadagno, small-celled purple sulfur bacteria related to Lamprocystis are present in significant numbers, up to 6 9 10 5 cells mL À1 , and often form aggregates with the sulfate-reducing bacteria affiliated to Desulfocapsa thiozymogenes (Peduzzi et al, 2003a;Tonolla et al, 2003;Decristophoris et al, 2009). This study showed for the first time, directly in the environment, that N 2 fixation is carried out by the rare green sulfur bacterium Chlorobium sp.…”
Section: Simultaneous Nanosims Imaging Of Identity and Metabolic Actimentioning
confidence: 99%
“…They can oxidize hydrogen sulfide to sulfate under anaerobic conditions during anoxygenic photosynthesis and grow autotrophically via the reductive pentose phosphate cycle (Biebl & Pfennig, 1979). In the chemocline of the oligotrophic Lake Cadagno, small-celled purple sulfur bacteria related to Lamprocystis are present in significant numbers, up to 6 9 10 5 cells mL À1 , and often form aggregates with the sulfate-reducing bacteria affiliated to Desulfocapsa thiozymogenes (Peduzzi et al, 2003a;Tonolla et al, 2003;Decristophoris et al, 2009). In situ measurements showed their ability of chemolithotrophic carbon fixation (Camacho et al, 2001).…”
Section: Simultaneous Nanosims Imaging Of Identity and Metabolic Actimentioning
confidence: 99%